A systemic approach for integrative design of buildings and landscapes: towards ecosystem services provision in urban areas - Silveira, Clarissa Ferreira Albrecht da (2018)
Cities are at the core of current environmental problems and, conversely, may host the solutions for them. They are the defining ecological phenomenon of the twenty-first century. Natural patterns and processes within cities might be a means toward an ecological regeneration of their bioregions through a symbiotic relationship between them. In this context, design has a great potential to reshape cities, transforming them for improved living conditions and balanced ecological systems. Considering buildings and landscapes as reciprocal entities within a system is a great opportunity for design innovation and increased performance with an active engagement between people and nature. By assuming the ecosystem services approach as a reference for highest ecological performance when multiple ecosystem services are provided within a system, this dissertation proposes an urban ecosystem services framework and the concept of service providing design for assessing architecture and landscape architecture. This framework is the basis to analyze three rating systems that are the most relevant standards for sustainable and regenerative design of architecture and landscape architecture, being the Living Building Challenge â , LEED â , and Sustainable SITES Initiative â . Furthermore, two architecture and landscape architecture certified and high-performance projects are analyzed. Based on the analysis, other ecosystem services beyond those proposed in the framework are identified, being renewable energy sources and active living. Some ecosystem services considered are not required by the rating systems, and not provided by the projects, being medicinal resources, pollination, and spiritual experience. Although required, food production is not provided in the projects studied due to a scale issue as they are located in densely occupied urban sites. Moreover, SITES is currently more related to ecosystem services than LEED, which suggests that the ecosystem services framework has a great potential as a tool to explore the relationship of building design criteria and natural systems and cycles. Although most ecosystem services are identified as provided by the two assessed projects, their performance suggests that they are not yet fully integrated to the natural ecosystem. This fact corroborates to the necessary next step for defining the Urban Ecosystem Services Framework in a quantitative approach with a hierarchical organization of the ecosystem services. Rigorously addressing the ecosystem services approach in LEED, SITES, and other rating systems will help integrate ecological regeneration processes in architecture, landscape architecture, and cities.